Perbandingan Pendapatan UMKM Kue Karasa: E-Commerce Versus Konvensional (Kecamatan Cempa, Kabupaten Pinrang) - Yuliana; Darmawan; Suherman (Integrated and Sustainable Agriculture, 2024)
This study aims to analyze and compare the feasibility of Karasa micro, small and medium enterprises (MSMEs) with e-commerce and conventional sales models in Cempa District, Pinrang Regency. The aspects analyzed include business costs, revenues, revenues, and business feasibility using the R/C ratio method. The results showed that both business models have business feasibility, but conventional sales models generate higher revenues compared to e-commerce models. This is due to several factors, such as the lack of understanding of business actors in operating e-commerce platforms and customer preferences to buy products directly.